2011
DOI: 10.1002/adfm.201002112
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin Nanocarriers Based on Magnetic Colloids with a Bio‐polyelectrolyte Corona and High Non‐linear Optical Response: Synthesis, Characterization, and Properties

Abstract: Magnetic drug nanocarriers are synthesized following an arrested mineralization of magnetic spinel iron oxides in the presence of the biopolymer of sodium carboxymethylcellulose. Based on the experimental results, the polyelectrolyte corona probably attains a brushlike configuration around the magnetic particles. The inner core of these colloids may be constituted of polymer‐associated nanocrystallites, forming nanogel colloids. The hybrid colloids are endowed with a high loading capacity for the anticancer ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 58 publications
1
29
0
Order By: Relevance
“…The stability with respect to ionic strength was tested by means of the variation of hydrodynamic diameter with different ionic strengths over a broad range of solution salinity (Figure A). The magnetic nanocluster cMNPs prepared in this work exhibit improved stability when compared with the nanoparticles prepared previously by Bakandritsos et al . The d H of the cMNPs exceeded 200 nm at 0.5 m concentration of NaCl whereas the MNPs prepared according to the original protocol exceeded the 200 nm limit of d H at 0.03 m NaCl.…”
Section: Resultsmentioning
confidence: 54%
See 3 more Smart Citations
“…The stability with respect to ionic strength was tested by means of the variation of hydrodynamic diameter with different ionic strengths over a broad range of solution salinity (Figure A). The magnetic nanocluster cMNPs prepared in this work exhibit improved stability when compared with the nanoparticles prepared previously by Bakandritsos et al . The d H of the cMNPs exceeded 200 nm at 0.5 m concentration of NaCl whereas the MNPs prepared according to the original protocol exceeded the 200 nm limit of d H at 0.03 m NaCl.…”
Section: Resultsmentioning
confidence: 54%
“…The transmission electron microscopy (TEM) images (Figure A) of the colloidal MNPs show their structural organization, demonstrating that the densely packed cMNPs are arranged into superclusters whereas the cMNPs prepared as described in the previous study by Bakandritsos et al . self‐assemble into chain‐like morphologies.…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…Recently, it has been shown that Au NPs can be produced using cellulose derivatives including cellulose ethers, methylhydroxyethyl cellulose, and carboxymethyl cellulose as reducing agents . In this work, CMC was used as a stabilizing agent for magnetite NPs according to the previously described protocol …”
Section: Methodsmentioning
confidence: 53%